1985
DOI: 10.1073/pnas.82.23.8039
|View full text |Cite
|
Sign up to set email alerts
|

Brain clathrin light chain 2 can be phosphorylated by a coated vesicle kinase.

Abstract: A protein kinase activity was observed in coated vesicles, prepared from bovine brain, that had clathrinassociated protein 2 (CAP2, also known as clathrin light chain 2) as its principal substrate. Coated vesicles were purified by sucrose density gradient centrifugation followed by Sephacryl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
40
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 28 publications
5
40
0
Order By: Relevance
“…Substitution of an acidic residue at the third position downstream of the serine in GGA2 allowed the molecule to be phosphorylated by CK2. Although the actual kinase that phosphorylates GGA1 and GGA3 in cells has yet to be identified, it should be noted that a CK2-type enzyme has been shown to be associated with clathrin-coated vesicles (16,(21)(22)(23)(24). In preliminary experiments, we found that an activity associated with purified clathrin-coated vesicles phosphorylates the GGA1 peptide.…”
Section: Discussionmentioning
confidence: 99%
“…Substitution of an acidic residue at the third position downstream of the serine in GGA2 allowed the molecule to be phosphorylated by CK2. Although the actual kinase that phosphorylates GGA1 and GGA3 in cells has yet to be identified, it should be noted that a CK2-type enzyme has been shown to be associated with clathrin-coated vesicles (16,(21)(22)(23)(24). In preliminary experiments, we found that an activity associated with purified clathrin-coated vesicles phosphorylates the GGA1 peptide.…”
Section: Discussionmentioning
confidence: 99%
“…AtT-20#1 cells stably expressing GAIP were prepared as described previously (25,27) and labeled for 4 h with either 100 Ci͞ml Easytag or 1 mCi͞ml [ 32 P]orthophosphate. 35 S labeling was performed in Cys-and Met-free DMEM supplemented with 4% dialysed FCS. 32 P labeling was carried out in phosphate-free DMEM supplemented with 4% FCS.…”
mentioning
confidence: 99%
“…Morphological alterations of the cell surface and cytoskeleton are among the earliest manifestations of the src gene product (Ambros et al, 1975; Boschek et al, 1981). Among the cell surface changes, it has been observed that a number of receptors, including those for epidermal growth factor and thrombin, are cleared from the surface by endocytic events that may be altered by pp60 ~-s~ (Decker, 1983;Cooper et al, 1983;Zetter et al, 1977).Endocytosis often proceeds via coated pits and coated vesicles (for review see Pastan and Willingham, 1985), structures whose coats are known to include several phosphoproteins, among them the assembly factor polypeptides (Pauloin et al, 1982;Campbell et al, 1984;Keen et al, 1987) and the clathrin light chains (Usami et al, 1985;Schook and Puszkin, 1985;Bar-Zvi and Branton, 1986 phorylation both in vivo and in vitro (Keen and Black, 1986; Bar-Zyi et al, 1988b), phosphorylation of clathrin heavy chain, the major component of coated vesicles, has not been observed in normal cells. Here we show that transformation of secondary chick embryo fibroblasts (CEF) by RSV induces the phosphorylation of clathrin heavy chains on tyrosine and serine residues.…”
mentioning
confidence: 99%
“…Endocytosis often proceeds via coated pits and coated vesicles (for review see Pastan and Willingham, 1985), structures whose coats are known to include several phosphoproteins, among them the assembly factor polypeptides (Pauloin et al, 1982;Campbell et al, 1984;Keen et al, 1987) and the clathrin light chains (Usami et al, 1985;Schook and Puszkin, 1985;Bar-Zvi and Branton, 1986 phorylation both in vivo and in vitro (Keen and Black, 1986; Bar-Zyi et al, 1988b), phosphorylation of clathrin heavy chain, the major component of coated vesicles, has not been observed in normal cells. Here we show that transformation of secondary chick embryo fibroblasts (CEF) by RSV induces the phosphorylation of clathrin heavy chains on tyrosine and serine residues.…”
mentioning
confidence: 99%